A Systematic Literature Review of Whistleblowing Intention: Variability, Research Trends, Methods, and Theories - Andrik Aprilyanto Setiawan; Harti Budi Yanti (Budapest International Research and Critics University, 2022)
Nothing in an organization is free from the threat of fraud, either individually or in groups to enrich themselves. Fraud prevention through the Whistleblowing system is a fairly effective instrument. Becoming a whistleblower is faced with the choice to report or not to report fraudulent acts that occur within the organization. There are many factors to consider whether the whistleblower reports the fraud. This literature review examines the empirical study literature related to a person's intention to report fraud. The aim is to provide information to academics, researchers, practicums, and the organization itself regarding the factors of a person's intention to report through whistleblowing. The Systematic Literature Review technique was used in three stages, namely the planning stage, conducting stage and reporting stage. Then, the literature review was compiled systematically starting with the search for studies from January 2018 to May 2022. Analysis related to Variability, Research Trends, Methods, and Theory used related to whistleblowing intention. The results are quantitative research methods by survey and the theory of planned behavior is the most widely used. And factors with the category of situational characteristics are the least used variables in this SLR research. Whereas, the independent variables that are most widely used in the journal whistleblowing intentions are attitude variables, perceived behavioral control, subjective norms, perceived organizational support, personal responsibility for reporting, independence commitment, and personal cost of reporting.